Method for flotation separation of carbon-lead bulk concentrate

Through ultrafine grinding and surface passivation technology, combined with multiple carbon sweeps of foaming agents and activators, the problem of carbon quality in carbon-containing lead sulfide zinc ore is solved, and high-grade lead concentrate and carbon essence are achieved The separation of ore simplifies the agent system, avoids the environmental hazards of potassium dichromate, and improves the separation efficiency.

CN119114287AActive Publication Date: 2024-12-13安徽铜冠产业技术研究院有限责任公司
6 Cites 0 Cited by

Patent Information

Application Number
CN202411430393.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-13
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The floatingability of carbonaceous in lead-zinc ores containing carbon sulfide lead-zinc flotation results in high consumption of agents during lead-zinc flotation, and carbonaceous enters concentrate products, resulting in low grade. In addition, existing methods for suppressing lead-floating carbon are mostly used to severely toxic Potassium chromate, harmful to the environment.

Method used

After ultrafine grinding, sulfuric acid, ferric chloride and alum are added for surface passivation, combined with foaming agent and activator for multiple carbon sweeps, and natural inorganic salts ferric chloride and alum are used to replace potassium dichromate to simplify The pharmaceutical system improves the grade of lead concentrate and the separation efficiency of carbon concentrate.

Benefits of technology

The lead concentrate grade is greater than 65%, and the lead recovery rate is greater than 98%, without additional inhibitors. The agent system is simplified, the harm of potassium dichromate to the environment is eliminated, and the carbon concentrate selection and separation efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114287A_ABST
    Figure CN119114287A_ABST
Patent Text Reader

Abstract

The invention relates to a flotation separation method for carbon-lead bulk concentrate, and belongs to the technical field of beneficiation, the method comprises the following steps: carrying out ultrafine grinding on the carbon-lead bulk concentrate, and adding water until the pulp concentration is 10-15%; sulfuric acid, ferric chloride and alums are sequentially added, air stirring is conducted, and the surface of galena in the carbon-lead bulk concentrate is passivated; a foaming agent (2 # oil) is added for carbon sweeping roughing to obtain carbon rough concentrate and roughing tailings, and the carbon rough concentrate and the roughing tailings are separately stored; and a foaming agent (2 # oil) is added into the roughing tailings for two times of carbon scavenging roughing, and scavenged tailings are lead concentrates. The lead grade of the obtained lead concentrate is greater than 65%, and the lead recovery rate is greater than 98%; the ferric chloride and the alum are adopted to carry out surface passivation and flocculation agglomeration on the galena, the separation of the carbon-lead bulk concentrate does not need to add an inhibitor to inhibit the galena, the reagent system of carbon-lead separation is simplified, and an ideal separation effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ore dressing, and in particular relates to a method for flotation separation of carbon-lead mixed concentrate. Background Art

[0002] In carbon-containing sulfide lead-zinc ores, due to the good natural floatability of carbon and its close connection with lead-zinc minerals, the lead-zinc flotation process will not only cause a large amount of reagent consumption, but also the carbon will easily enter the lead-zinc concentrate product, resulting in a low grade of the lead-zinc concentrate product and difficulty in obtaining qualified products.

[0003] Usually for carbon-containing lead-zinc ores, current process technologies generally use three methods to eliminate the influence of carbon on lead-zinc flotation: pre-decarbonization, carbon suppression for direct floatation of lead and zinc, and carbon-lead mixed floatation and then separation. There are relatively few studies on lead suppression and carbon floating. Usually, potassium dichromate is used for lead suppression and carbon floating, and the effect is relatively ideal. However, potassium dichromate is a highly toxic substance and has great harm to the environment. Summary of the invention

[0004] The object of the present invention is to provide a method for flotation separation of carbon-lead mixed concentrate in order to solve the above-mentioned problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] The present invention provides a method for flotation separation of a carbon-lead mixed concentrate, comprising the following steps:

[0007] Step S1, after ultrafine grinding of the carbon-lead mixed concentrate, water is added to the slurry concentration to be 10-15%;

[0008] Step S2, adding sulfuric acid, ferric chloride and alum in sequence and aerating and stirring to passivate the surface of the galena in the carbon-lead mixed concentrate;

[0009] Step S3, adding a foaming agent (No. 2 oil) to perform carbon sweep roughing to obtain a carbon rough concentrate and a roughing tailing, and storing the carbon rough concentrate and the roughing tailing separately;

[0010] Step S4, adding a frother (No. 2 oil) to the roughing tailings to perform two carbon sweep roughings, and the sweeping tailings are lead concentrates;

[0011] Step S5, adding an activator to the carbon rough concentrate for soaking and selection, adding the selection solution three times, at 12h, 24h and 36h of soaking respectively, taking out after 48h of soaking, flushing with river water until no activator remains on the surface, and obtaining carbon concentrate.

[0012] As a further optimization scheme of the present invention, the lead grade of the carbon-lead mixed concentrate is 45.67%-52.64%, the carbon grade is 3.81%-6.88%, the lead concentrate is galena, the carbon concentrate is elemental organic carbon and carbonaceous shale, the fineness is 55%-0.074 mm, and the monomer dissociation degree of the lead mineral is 95%; the grinding fineness of the carbon-lead mixed concentrate is (90%-95%)-0.015 mm, and the slurry concentration is 10-15%.

[0013] As a further optimization scheme of the present invention, the amount of sulfuric acid is 500-800 g / t, the pH value of the slurry is adjusted to 4-5, and then 1000-1500 g / t of ferric chloride and 500-1000 g / t of alum are added, and aeration and stirring are carried out for 22-26 hours.

[0014] As a further optimization scheme of the present invention, the amount of the carbon sweep roughing foaming agent (No. 2 oil) is 30-50g / t, the amount of the first carbon sweep roughing No. 2 oil is 10-20g / t, and the amount of the second carbon sweep roughing No. 2 oil is 10-15g / t.

[0015] As a further optimization scheme of the present invention, the foaming agent (No. 2 oil) is one of butyl xanthate or pine alcohol oil.

[0016] As a further optimization scheme of the present invention, the preparation process of the activator is: sodium hydroxide, quicklime, ore powder, cellulose, fermented wheat straw and pure water are mixed, injected into a fermentation tank, fermented for 1-2 days, and taken out to obtain the activator.

[0017] As a further optimization scheme of the present invention, the raw materials for preparing the activator include, by weight: 20-35 parts of sodium hydroxide, 45-50 parts of quicklime, 15-35 parts of ore powder, 5-10 parts of cellulose, 8-16 parts of fermented wheat straw and 70-85 parts of pure water.

[0018] As a further optimization scheme of the present invention, the preparation process of the ore powder is: grinding arsenopyrite, tungsten ore and volcanic rock, sieving, and taking particles with a particle size of 1-3 cm as ore powder.

[0019] As a further optimization scheme of the present invention, the raw materials for preparing the ore powder include, by weight: 30-35 parts of arsenopyrite, 20-30 parts of tungsten ore and 15-28 parts of volcanic rock.

[0020] The beneficial effects of the present invention are:

[0021] (1) The lead grade of the lead concentrate obtained by the present invention is greater than 65%, and the lead recovery rate is greater than 98%;

[0022] (2) Ferric chloride and alum are used to passivate the surface of galena and flocculate it. The separation of carbon-lead mixed concentrate does not require the addition of inhibitors to inhibit galena, which simplifies the reagent system for carbon-lead separation and achieves an ideal separation effect.

[0023] (3) The carbon-lead mixed coarse concentrate was ultra-finely ground to a fineness of 90% to 95% - 0.015 mm, which not only increased the specific surface area of ​​the galena mineral, which was beneficial to its surface passivation, but also played a role in surface scrubbing and drug removal, making it easier to separate carbon from lead;

[0024] (4) Ferric chloride and alum are natural inorganic salts, non-toxic and environmentally friendly, eliminating the potential harm to human body and environment when using a large amount of potassium dichromate as galena inhibitor;

[0025] (5) The beneficiation solution is added three times, at 12 h, 24 h and 36 h of soaking respectively. The mixture is taken out at 48 h of soaking and washed with river water until no activator remains on the surface to obtain carbon concentrate. Adding the beneficiation solution in three stages can increase the amount of carbon concentrate selected. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of the method for separating the carbon-lead mixed concentrate. DETAILED DESCRIPTION

[0027] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0028] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.

[0029] The preparation process of the fermented wheat straw shreds of the present invention is as follows: taking seasonal wheat straw, breaking it into pieces with a length of 2-3 cm; placing the wheat straw shreds in an open-air container, adding water to cover the wheat straw shreds, fermenting for 15 days, filtering out the water, and obtaining the fermented wheat straw shreds.

[0030] Example 1

[0031] The lead grade of the carbon-lead mixed concentrate is 45.67%, the carbon grade is 6.88%, the lead concentrate is galena, the carbon concentrate is elemental organic carbon and carbonaceous shale, the fineness is 55%-0.074 mm, and the monomer dissociation degree of the lead mineral is 95%;

[0032] The carbon-lead mixed concentrate is ground to 95%-0.015 mm, water is added to the pulp concentration to 15%, and then 600g / t sulfuric acid, 1100g / t ferric chloride and 500g / t alum are added to the pulp in sequence, and the surface of the galena is passivated by aeration and stirring for 24 hours;

[0033] After the surface of galena is passivated, 40g / t No. 2 oil is added to the pulp in sequence for carbon sweeping and roughing to obtain carbon rough concentrate and roughing tailings. No. 2 oil is added to the roughing tailings for two carbon sweeping and roughing, the first time with 20g / t No. 2 oil, the second time with 10g / t No. 2 oil, sweeping tailings to obtain lead concentrate. The carbon rough concentrate is subjected to three rounds of selection to obtain lead concentrate. The selection process is as follows: an activator is added to the carbon rough concentrate for soaking and selection. The selection solution is added three times, at 12h, 24h and 36h of soaking respectively, and taken out at 48h of soaking, and washed with river water until there is no activator residue on the surface to obtain carbon concentrate;

[0034] The preparation process of the activator is as follows: 20 parts of sodium hydroxide, 45 parts of quicklime, 15 parts of ore powder, 5 parts of cellulose, 8 parts of fermented wheat straw and 70 parts of pure water are mixed, injected into a fermentation tank, fermented for 1 day, and taken out to obtain the activator;

[0035] The preparation process of the ore powder is as follows: 30 parts of arsenopyrite, 20 parts of tungsten ore and 15 parts of volcanic rock are ground, sieved, and particles with a particle size of 1-3 cm are taken as ore powder.

[0036] Comparative Example 1

[0037] Potassium dichromate was used as a galena inhibitor in the separation of carbon-lead mixed concentrate. The carbon-lead mixed concentrate was ground to 95%-0.045 mm, slurried to a pulp concentration of 15%, and 8000g / t potassium dichromate, 40g / t kerosene, and 30g / t No. 2 oil were added in sequence for carbon scavenging roughing to obtain carbon rough concentrate and roughing tailings. Kerosene was added to the roughing tailings for scavenging, 15g / t kerosene was added to scavenging one, and 10g / t kerosene was added to scavenging two. Lead concentrate was obtained from the scavenging tailings. Potassium dichromate was added to the carbon rough concentrate for three times of concentrating to obtain carbon concentrate. The lime dosages in concentrating one, concentrating two, and concentrating three were 5000g / t, 2000g / t, and 1000g / t, respectively.

[0038] The test results of Example 1 and Comparative Example 1 are shown in Table 1

[0039] Table 1 Test results of Example 1 and Comparative Example 1 (%)

[0040]

[0041] Example 2

[0042] A carbon-lead mixed concentrate has a lead grade of 52.64% and a carbon grade of 3.81%. The lead concentrate is galena, and the carbon concentrate is elemental organic carbon and carbonaceous shale. The fineness is 60%-0.074 mm, and the monomer dissociation degree of the lead mineral is 95%;

[0043] The carbon-lead mixed concentrate is ground to 95%-0.015 mm, water is added to the pulp concentration to 15%, and then 800g / t sulfuric acid, 1500g / t ferric chloride and 600g / t alum are added to the pulp in sequence, and the surface of the galena is passivated by aeration and stirring for 24 hours;

[0044] After the surface of galena is passivated, 45g / t No. 2 oil is added to the pulp in sequence for carbon sweeping and roughing to obtain carbon rough concentrate and roughing tailings. No. 2 oil is added to the roughing tailings for two carbon sweeping and roughing, with 25g / t No. 2 oil added for the first time and 15g / t No. 2 oil added for the second time. The tailings are swept to obtain lead concentrate. The carbon rough concentrate is subjected to three rounds of selection to obtain lead concentrate. The selection process is as follows: an activator is added to the carbon rough concentrate for soaking and selection. The selection solution is added three times, at 12h, 24h and 36h of soaking respectively, and taken out at 48h of soaking. The carbon concentrate is washed with river water until there is no activator residue on the surface to obtain carbon concentrate.

[0045] The preparation process of the activator is as follows: 35 parts of sodium hydroxide, 50 parts of quicklime, 35 parts of ore powder, 10 parts of cellulose, 16 parts of fermented wheat straw and 85 parts of pure water are mixed, injected into a fermentation tank, fermented for 2 days, and taken out to obtain the activator;

[0046] The preparation process of the ore powder is as follows: 35 parts of arsenopyrite, 30 parts of tungsten ore and 28 parts of volcanic rock are ground, sieved, and particles with a particle size of 1-3 cm are taken as ore powder.

[0047] Comparative Example 2

[0048] Potassium dichromate was used as a galena inhibitor in the separation of carbon-lead mixed concentrate. The carbon-lead mixed concentrate was ground to 95%-0.045 mm, slurried to a pulp concentration of 15%, and 6000g / t potassium dichromate, 30g / t kerosene, and 25g / t No. 2 oil were added in sequence for carbon scavenging roughing to obtain carbon rough concentrate and roughing tailings. Kerosene was added to the roughing tailings for scavenging, 18g / t kerosene was added to scavenging one, and 15g / t kerosene was added to scavenging two. Lead concentrate was obtained from the scavenging tailings. Potassium dichromate was added to the carbon rough concentrate for three times of concentrating to obtain carbon concentrate. The lime dosages in concentrating one, concentrating two, and concentrating three were 4000g / t, 2000g / t, and 2000g / t, respectively.

[0049] The test results of Example 2 and Comparative Example 2 are shown in Table 2.

[0050] Table 2 Test results of Example 2 and Comparative Example 2 (%)

[0051]

[0052] Under weakly acidic and aerobic conditions, Fe3+ in FeCl3 undergoes a strong redox reaction with galena, producing active Fe2+ in the galena surface lattice. The active Fe2+ will be rapidly oxidized to Fe3+ and react with K- and Reaction, forming a dense layer of yellow potassium ferroaluminate (KFe 3 (SO 4 ) 2 (OH) 6 ) passivation film makes galena hydrophilic and its floatability is inhibited. The main chemical reaction process is as follows:

[0053] PbS+2Fe 3+ →0.125S 8 +2Fe 2+ +Pb 2+

[0054] 2Fe 2+ +0.5O 2 +2H + →2Fe 3+ +H 2 O

[0055]

[0056] Potassium ferroaluminate (KFe 3 (SO 4 ) 2 (OH) 6 ) has great hydrophilicity, and the surface of galena forms yellow potassium ferroaluminate (KFe 3 (SO 4 ) 2 (OH) 6 ) After the passivation film is formed, its hydrophilicity is greatly improved. At the same time, the Al3+ in alum has a flocculation and agglomeration effect on the fine-grained galena after surface passivation, which further increases its hydrophilicity, making it difficult for the collector to adsorb on its surface. Therefore, there is no need to add additional lead inhibitor when separating the carbon-lead mixed concentrate.

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for flotation separation of carbon-lead mixed concentrate, characterized in that: The following steps are involved: Step S1, after ultrafine grinding of the carbon-lead mixed concentrate, water is added to the slurry concentration to be 10-15%; Step S2, adding sulfuric acid, ferric chloride and alum in sequence and aerating and stirring to passivate the surface of the galena in the carbon-lead mixed concentrate; Step S3, adding a foaming agent (No. 2 oil) to perform carbon sweep roughing to obtain a carbon rough concentrate and a roughing tailing, and storing the carbon rough concentrate and the roughing tailing separately; Step S4, adding a frother (No. 2 oil) to the roughing tailings to perform two carbon sweeping roughings, and the sweeping tailings are lead concentrates; Step S5, adding an activator to the carbon rough concentrate for soaking and selection, adding the selection solution three times, at 12h, 24h and 36h of soaking respectively, taking out after 48h of soaking, flushing with river water until no activator remains on the surface, and obtaining carbon concentrate.

2. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The lead grade of the carbon-lead mixed concentrate is 45.67%-52.64%, and the carbon grade is 3.81%-6.88%. The lead concentrate is galena, and the carbon concentrate is elemental organic carbon and carbonaceous shale. The fineness is 55%-0.074 mm, and the monomer dissociation degree of the lead mineral is 95%; the grinding fineness of the carbon-lead mixed concentrate is (90%-95%)-0.015 mm, and the slurry concentration is 10-15%.

3. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The amount of sulfuric acid used is 500-800 g / t, the pH value of the slurry is adjusted to 4-5, and then 1000-1500 g / t of ferric chloride and 500-1000 g / t of alum are added, and the mixture is aerated and stirred for 22-26 hours.

4. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The amount of the carbon sweep roughing foaming agent (No. 2 oil) is 30-50g / t, the amount of the first carbon sweep roughing No. 2 oil is 10-20g / t, and the amount of the second carbon sweep roughing No. 2 oil is 10-15g / t.

5. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The foaming agent (No. 2 oil) is one of butyl xanthate or pine alcohol oil.

6. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The preparation process of the activator is as follows: sodium hydroxide, quicklime, ore powder, cellulose, fermented wheat straw pieces and pure water are mixed, injected into a fermentation tank, fermented for 1-2 days, and taken out to obtain the activator.

7. The method for flotation separation of a carbon-lead mixed concentrate according to claim 6, characterized in that: The raw materials for preparing the activator include, by weight: 20-35 parts of sodium hydroxide, 45-50 parts of quicklime, 15-35 parts of ore powder, 5-10 parts of cellulose, 8-16 parts of fermented wheat straw pieces and 70-85 parts of pure water.

8. The method for flotation separation of a carbon-lead mixed concentrate according to claim 1, characterized in that: The preparation process of the ore powder is as follows: arsenopyrite, tungsten ore and volcanic rock are ground, sieved, and particles with a particle size of 1-3 cm are taken as ore powder.

9. The method for flotation separation of a carbon-lead mixed concentrate according to claim 8, characterized in that: The raw materials for preparing the ore powder include, by weight: 30-35 parts of arsenopyrite, 20-30 parts of tungsten ore and 15-28 parts of volcanic rock.

Citation Information

Patent Citations

  • Method for selectively recovering lead from pregnant solution containing cyanides and heavy metals

    CN102242269A

  • Preparation method of soil passivator

    CN110003915A

  • Straw modified biochar as well as preparation method and application thereof

    CN112717881A

  • Mineral type porous adsorption ore-based biochar as well as preparation method and application thereof

    CN116621169A

  • Method for obtaining cryptocrystalline graphite concentrate from carbon-containing sulphide ore decarburized tailings

    CN116689145A